Красота уходящая: фотокнига / Белых, Валенин Леонидович; текст С.А. Жилина - Белых Валентин Леонидович (Книга Приуралья, 2024)
Экземпляры: К. Х (20240503) / Инвентарный номер: 50294 / Цена: 600.00 / Сис.шифр: 85.143(2Рос.Удм) / Авт.знак: Б 43 / ГРНТИ: 18 / ББК: 85.143(2Рос.Удм)